BETWEEN PLANNING AND DEMOCRACY: BUDGETING, CITIZEN PARTICIPATION, AND THE GIS CYCLE - Cavalcante, Ailton Ferreira (Seven Editora, 2026)
Public budgeting is the primary instrument through which governments transform political choices into fundable priorities and concrete actions. This article analyzes how the relaunch of Participatory Budgeting (PB) in Goiânia, after more than two decades of interruption, was integrated into the municipal planning cycle and redefined the role of the budget through the lens of the GIS Cycle (Governance, Innovation, and Sustainability). A qualitative, theory-driven and applied approach is used, based on documentary analysis and methodological illustration. The study examines the articulation between PB, the Multi-Year Plan (PPA 2026–2029), the Budget Guidelines Law (LDO), and the Annual Budget Law (LOA 2026), alongside technical training initiatives, Objectives and Key Results (OKRs), transparency mechanisms, and continuous monitoring. Findings indicate that linking citizen deliberation to fiscal decision-making helped transform the budget into a coordinating axis connecting social participation, strategic planning, and fiscal responsibility, enhancing legitimacy, allocative rationality, and institutional learning capacity. Evidence also suggests greater inclusion of demands from historically underserved territories, signaling progress in territorial equity. Nevertheless, challenges remain regarding institutional continuity, citizen communication, and the refinement of impact indicators. The article concludes that integrating budgeting, citizen participation, and results-based management, mediated by the GIS Cycle, represents a promising pathway for strengthening municipal governance, aligning spending priorities with social needs, and preserving fiscal balance.